APPLICATION OF DIGITAL STRUCTURE SIMULATION AS A TOOL FOR THE EXPLORATION OF WIDE SPAN STRUCTURE IDEAS - Shirley Wahadamaputera; Bambang Subekti; Dian Duhita Permata (MODUL, 2021)
Review on structure behaviour and visual appearance of a building is needed in generating creativity in the making of an architectural design. The use of any specific structure software will facilitate this in the process. This research aims to prove the effectiveness with which designers can compose alternative forms of architectural appearance through the use of the software. One of the tools in the creative process used in the exploration of 2-dimensional frame structures is DR FRAME. The observations were carried in the Structure and Construction IV Studio at Itenas Architecture Study Program Bandung through a digital simulation using DR. FRAME software demo version. Several students are invited to explore various forms of wide-span truss structures at the level of unified integration. The results through the program execution show various diagrams which can be implemented in the design of the form and the type of structural components. DR.FRAME software enriches ideas in the wide-span structure design which provides an understanding of the relationship between structural behaviour and the appearance of architectural design. The use of other supporting software is supposed to be applied as an alternative search for various structural design ideas for architecture students